Floral visitors and reproductive strategies in five melittophilous species of Bignoniaceae in Southeastern Brazil - Yuriko A. N. Pinto Yanagizawa (Brazilian Archives of Biology and Technology, 2007)
In order to evaluate the pollination strategies of Bignoniaceae, the floral biology and the floral visitors in five species, three cerrado shrubs (Arrabidaea brachypoda (DC.) Bor., Jacaranda decurrens Cham., and Jacaranda oxyphylla Cham.), and two lianas from the border of a semideciduous seasonal forest (Arrabidaea samydoides (Cham.) Sandw., and Arrabidaea triplinervia H. Baill.) were studied in Botucatu, São Paulo State, Southeastern Brazil. The flowering periods were partially overlapping, especially between species in the same habitat. All the five species were functionally allogamous, melittophilous, nototribic and mainly pollinated by long tongued large bees. Some medium-sized and small pollen-foraging bees were occasional legitimate visitors, whereas others visitors were robbers/thieves. Each species showed a particular set of pollinators. Only two pollinator species were observed in more than one bignon. There was no partition of pollinators even among the species of bignons blooming at the same time at the same habitat. Com objetivo de avaliar as estratégias de polinização de espécies de Bignoniaceae, foram estudados a biologia floral e os visitantes florais de cinco espécies, três arbustivas do cerrado (Arrabidaea brachypoda (DC.) Bor., Jacaranda decurrens Cham. e Jacaranda oxyphylla Cham.) e duas lianas da orla da floresta estacional semidecidual (Arrabidaea samydoides (Cham.) Sandw. e Arrabidaea triplinervia H. Baill.), na região de Botucatu (22º52'20" S e 48(0)26'37" W), estado de São Paulo, sudeste do Brasil. Os períodos de florescimento, principalmente entre espécies do mesmo habitat, apresentaram sobreposição parcial. Observou-se que as cinco espécies são alogâmicas funcionais, melitófilas, nototríbicas, polinizadas principalmente por abelhas grandes de língua comprida. Algumas abelhas coletoras de pólen de tamanho médio e pequeno atuaram como polinizadoras ocasionais, enquanto outros visitantes foram pilhadores. Cada uma das Bignoniaceae apresentou um conjunto particular de polinizadores havendo apenas duas espécies comuns a mais de uma delas. Não houve partilha de polinizadores mesmo entre bignoniáceas que, no mesmo habitat, apresentaram períodos de florescimento simultâneo.